PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, KEBIJAKAN DIVIDEN, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Fakhrana Oktaviarni (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2018)
This research aims to empirically examine the effects of profitability, liquidity, leverage, dividend regulation, and company size on company’s firm value. Population of this research are companies in real estate, property, and building construction sector that are listed on Bursa Efek Indonesia during 2014-2016. Sample is determined by purposive sampling method which result in twenty-two companies involved in this research. Type of data used in this research is secondary data that was accessed through www.idx.co.id. Method of analysis in this research is multiple regression analysis. Result of this research shows that profitability ratio measured by Return on Assets, liquidity measured by Current Ratio, dividend regulation represented by Dividend Payout Ratio, and company size measured by natural logarithm of total assets affect company’s firm value, while leverage measured by Debt to Equity Ratio does not have effect on company’s firm value. Keywords: firm values, profitability, liquidity, leverage, dividend regulaton, company's size